Efficacy of HPV vaccine in preventing cervical cancer in the Tomsk region - O. A. Ananina; L. A. Kolomiets; L. D. Zhuykova; O. N. Churuksaeva; A. L. Chernyshova; A. B. Villert; L. V. Pikalova; V. Yu. Mosolkov (ABV-press, 2023)
Background. The age-standardized cervical cancer incidence rate in the Tomsk region in 2021 was consistently higher than the average for the Russian Federation (21.2 / 100,000 versus 13.6 / 100,000 women). Primary prevention of cervical cancer is best achieved by human papillomavirus (HPV) vaccination of girls.   Aim. To evaluate HPV vaccine efficacy for the prevention of cervical cancer in the Tomsk region within the framework of implementation of two regional programs: "Prevention of gynecological cancer and rehabilitation of women diagnosed with gynecological cancer in 2008-2010" and "Urgent measures to improve cancer care for the population of the Tomsk region in 2011-2013".   Material and methods. We studied the tolerability and efficacy of HPV vaccination for the prevention of HPV-associated cervical cancer in 439 vaccinated girls aged 9-26 years during a follow-up time of 14-years.   Results. The assessment of a 14-year follow-up study of the impact of HPV vaccination on HPV-associated cervical lesions has shown that HPV vaccine is safe and 100 % effective.   Conclusion. Further prospects for primary prevention of cervical cancer before the introduction of vaccines against HPV infection in the national immunization schedule indicates the feasibility and real clinical effectiveness of the introduction of regional and regional programs with the development of a mathematical model for optimizing financial costs for primary prevention of cervical cancer, taking into account demographic parameters and socio-economic damage from cervical cancer in the study area.